2020
DOI: 10.18596/jotcsa.569960
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterisation and In Silico Toxicity Evaluations of Thiocarbamates, Isothiocyanates, Nitrile, Glucosinolate and Lipids from Moringa oleifera Lam. Seed

Abstract: The phytochemical composition of medicinal plants is responsible for the ethnopharmacological applications. These phytochemicals vary in plants of same species planted in various geographical locations. The seed of Moringa oleifera Lam., a widely consumed multi-medicinal plant was examined for the bioactive phytochemicals. With the aid of Nuclear Magnetic Resonance (1 H-NMR/ 13 C-NMR) spectrometer, Electrospray Ionisation Mass Spectrometry (ESI-MS) and Fourier Transform Infrared (FT-IR) spectroscopy, the phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Previous work indicated that the seed extracts with high lipid content possess good antioxidant and low proteinase inhibition potentials, among others (Atolani et al, 2018), other studies (Njan et al, 2018) further revealed that the alcoholic extract of the M. oleifera seed could induce infertility in the male animal by attenuating semen pH, whilst also exhibiting hepatotoxic effects due to persistent increase in ALP and AST even after withdrawal of the extract being administered. We further reported that the seed extractives exhibited high renal toxicity in another (Olorundare et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous work indicated that the seed extracts with high lipid content possess good antioxidant and low proteinase inhibition potentials, among others (Atolani et al, 2018), other studies (Njan et al, 2018) further revealed that the alcoholic extract of the M. oleifera seed could induce infertility in the male animal by attenuating semen pH, whilst also exhibiting hepatotoxic effects due to persistent increase in ALP and AST even after withdrawal of the extract being administered. We further reported that the seed extractives exhibited high renal toxicity in another (Olorundare et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…The seeds of Moringa oleifera were obtained as previously indicated (Atolani et al, 2020). The seed was authenticated and documented with the voucher number UILH/002/1008 at the herbarium of the Department of Plant Biology, University of Ilorin, Nigeria.…”
Section: Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations